2018
DOI: 10.1002/dmrr.3068
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a distinct phenotype of elderly latent autoimmune diabetes in adults: LADA China Study 8

Abstract: Elderly LADA differs phenotypically and genetically from Y-LADA but has a clinical and genetic profile more similar to that of E-T2D. These distinct phenotypes could potentially help physicians better manage patients with E-LADA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
2
26
1
Order By: Relevance
“…Although metabolic syndrome has been described in LADA patients, obesity, dyslipidaemia and hypertension are less frequent in LADA patients than in T2D patients . Prior suggestions that LADA and T2D patients might be at similar risk of CV events implied that there might have been a different impact of the traditional CV risk factors in LADA patients.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although metabolic syndrome has been described in LADA patients, obesity, dyslipidaemia and hypertension are less frequent in LADA patients than in T2D patients . Prior suggestions that LADA and T2D patients might be at similar risk of CV events implied that there might have been a different impact of the traditional CV risk factors in LADA patients.…”
Section: Discussionsupporting
confidence: 68%
“…Although metabolic syndrome has been described in LADA patients, obesity, dyslipidaemia and hypertension are less frequent in LADA patients than in T2D patients. [25][26][27] Prior suggestions that LADA and T2D patients might be at similar risk of CV events implied that F I G U R E 2 Post-hoc Cox regression analysis of LADA and T2D participants in the UKPDS with respect to MACE and CV death at the end of the trial and at the end of the trial plus post-trial monitoring period. Abbreviations: CV, cardiovascular; LADA, latent autoimmune diabetes of adults; MACE, major adverse cardiovascular events; Met, metformin; SU, sulphonylurea, T2D, type 2 diabetes there might have been a different impact of the traditional CV risk factors in LADA patients.…”
Section: Effect Of Assigned Glycaemic Strategy On CV Outcomes By Lamentioning
confidence: 99%
“…Those LADA patients were separated in two groups in accordance with the onset of diabetes over or under 60 years of age, LADA‐Elderly, and LADA‐Young, respectively. LADA‐E compared with LADA‐Y had better residual β‐cell function, higher insulin resistance, more serious metabolic syndrome characteristics, similar proportion of islet autoantibody positivity, and, strikingly, different HLA‐DQ genetic background …”
Section: Discussionmentioning
confidence: 97%
“…However, there are abundant variations in the genotypes and the prevalence of islet autoantibodies in T1D patients across different races. Our previous study indicated that the age of onset contributes to the clinical heterogeneity in slow‐onset patients with T1D . It also has been shown that the level of C‐peptide at diagnosis is independently associated with the age of onset but also with HLA genotypes .…”
Section: Introductionmentioning
confidence: 96%